2014
DOI: 10.1103/physreve.89.013106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of front-surface target structures on properties of relativistic laser-plasma electrons

Abstract: We report the results of a study of the role of prescribed geometrical structures on the front of a target in determining the energy and spatial distribution of relativistic laser-plasma electrons. Our 3D PIC simulation studies apply to short-pulse, high intensity laser pulses, and indicate that a judicious choice of target front-surface geometry provides the realistic possibility of greatly enhancing the yield of high energy electrons, while simultaneously confining the emission to narrow (< 5• ) angular cone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 69 publications
3
61
0
Order By: Relevance
“…Front surface structures, such as towers and near-critical density plasmas, have shown an enhancement in proton energy as well [15][16][17][18] . Micro-wire array targets were suggested to create a highly directed energetic electron beam with enhanced bremsstrahlung radiation 19,20 . The use of hollow cylindrical targets has been demonstrated to produce bright x-rays and attosecond pulses 21, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Front surface structures, such as towers and near-critical density plasmas, have shown an enhancement in proton energy as well [15][16][17][18] . Micro-wire array targets were suggested to create a highly directed energetic electron beam with enhanced bremsstrahlung radiation 19,20 . The use of hollow cylindrical targets has been demonstrated to produce bright x-rays and attosecond pulses 21, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The narrowing of the electron angular distribution occurs due to guiding by the structures as explained in [42]. The electrons are guided along the structures by counteracting quasistatic magnetic and electric fields which arise due to the large currents and charge separation in the plasma.…”
Section: B Electron Angular Distributionmentioning
confidence: 99%
“…The physics behind the enhancements by the tower targets is discussed thoroughly in [42]. The enhancement to the energy distribution arises because electrons are injected directly into the laser field from the solid density target rather than from low density pre-plasma near the critical surface.…”
Section: B Electron Angular Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that electrons can also be guided by the cylinders due to the self-generated electrostatic and magnetic fields in the vicinity of the structures [14] .…”
Section: Micro-cylinder Targets-manipulating Laser-electron Accelerationmentioning
confidence: 99%